An Empirical Assessment of Workload and Migrants' Health in Germany - Kai Ingwersen; Stephan L. Thomsen (Institute of Labor Economics (IZA), 2020)
Workload and its physical and mental burden can have detrimental effects on individual health. As different jobs are associated with specific patterns of health development, occupational selection of socioeconomic groups can be attributed to health differences in society. Despite a long economic literature that has established native-migrant differences in occupational choice and health behaviour, surprisingly little research so far has been devoted to workload differences and the influence on individual health in this context. We consider differences in workload and related health status for migrants and native Germans through a detailed characterisation of occupational conditions. Based on labour force survey data for the years 2006, 2012 and 2018, our analysis takes a comprehensive set of work-related aspects into account, e.g., work tasks, job requirements, and working conditions. The empirical results show an enhanced perception of workload and related health problems among migrants. Working at the capacity limit has a particularly strong effect on emotional exhaustion, which is countered by a good working atmosphere being beneficial to health. Native Germans are more heavily burdened by high job requirements than migrants, both physically and mentally. However, as job-related factors show similar effects on the health status of males, the poorer health status of migrants could therefore be attributed to a lower utilization of health services.
Keywords: I14; J15; J81; 330; workload; working conditions; migrants; self-reported health; BIBB/BAuA